A narrative review of the safety concerns of deprescribing in older adults and strategies to mitigate potential harms. Issue 1 (2nd January 2018) - Reeve, Emily; Moriarty, Frank; Nahas, Rayan; Turner, Justin P.; Kouladjian O'Donnell, Lisa; Hilmer, Sarah N.
ABSTRACT: Introduction : As with prescribing or continuing medications, deprescribing brings with it the potential for harm as well as benefit. Uncertainty and avoidance of harm has been reported as a barrier to deprescribing in practice and may contribute to continuation of inappropriate medications. Areas covered : This narrative review covers four main safety concerns/potential harms of deprescribing in older adults: adverse drug withdrawal events, return of medical condition(s), reversal of drug-drug interactions and damage to the doctor-patient relationship. These are discussed in relation to medications in general, with some examples of medication classes used to illustrate the potential safety concerns. The majority of these harms can be minimized or even prevented by using a patient-centered, structured deprescribing process with planning, tapering and close monitoring during, and after medication withdrawal. Expert opinion : More research is needed into the safety concerns of deprescribing, however, avenues exist during drug development and post-marketing surveillance to gain knowledge on this topic. Questions remain about when it is suitable to discontinue certain medications/medication classes and there is uncertainty about the harms and benefits of both medication continuation and discontinuation in complex older adults.